Умумтаълим мактабларининг 5-синф ўқувчиларида информатикадан билимларни ўзлаштириш сифатини ошириш муаммоси - Тлегенов, Б.Н (SCIENCE and SOCIETY, 2020)
The article discusses the basic concepts of problem-based teaching, its essence, the functions of problem teaching, methods, tasks, problem lesson structure and other issues.
Keywords: education; knowledge; skill; experience; problem-based teaching; essence; functions; technology; methods; tasks; struc- ture; lesson